Ultrasensitive lateral flow assays for quantitative analysis - Koskela, Sonja (My University, 2023)
Acute myocardial infarction (AMI), also known as a heart attack, is a major cause of death. The aim of this master`s thesis project is to develop a sensitive and quantitative lateral flow assay (LFA) for the detection of an AMI biomarker, cardiac troponin I (cTnI) with the sensitivity of < 10 ng/L. Two proteins in human plasma, immunoglobulin M (IgM) and C1q, will be investigated as potential causes for the matrix effect in the cTnI LFA. A cTnI LFA was performed for the standard curves of cTnI in buffer, lithium heparin (LiHep) plasma and LiHep plasma treated with a solution, referred as the Clean-up kit, that is designed to remove IgM and rheumatoid factors from blood samples. The specific photoluminescence signals measured of LiHep plasma were lower than the specific signals measured of the two other sample matrixes, which indicates the matrix effect. The calculated LoD values for cTnI were 6.11 ng/L (in buffer), 12.36 ng/L (in LiHep plasma) and 3.79 ng/L (in LiHep plasma treated with the Clean-up kit). IgM did not bind to the anti-cTnI antibodies. C1q bound to the anti-cTnI antibodies but did not decrease the photoluminescence signal levels. Both IgM and C1q do not cause interference in the cTnI LFA. Although the cause of the matrix effect still needs to be discovered, the cTnI LFA shows great potential to be used for the quick diagnosis of AMI in the future.
Keywords: cardiac troponin I, acute myocardial infarction, lateral flow assay, IgM, C1q, matrix effect